Major complications of cryoballoon catheter ablation for atrial fibrillation and their management. (September 2014) - Bhat, Tariq; Baydoun, Hassan; Asti, Deepak; Rijal, Jharendra; Teli, Sumaya; Tantray, Mohmad; Bhat, Hilal; Kowalski, Marcin
<x xml:space="preserve">Abstract</x> Atrial fibrillation (AF) is the most common symptomatic and sustained cardiac arrhythmia. It affects approximately 2–3 million people in the USA alone with an increased incidence and prevalence worldwide. It is associated, in addition to worsening quality of life, with increased morbidity and mortality especially in poorly controlled AF, affecting mostly those older than 65 years of age. Radiofrequency ablation was found to be a good strategy for focal isolation of pulmonary veins triggering from the vulnerable atrial substrate but is a time-consuming procedure and carries the risk of multiple complications like tamponade which could be fatal, atrioesophageal fistula and local thrombus formation at the site of ablation. Cryoballoon ablation with pulmonary vein isolation has emerged in the past few years as a breakthrough novel technology for the treatment of drug-refractory AF. It is a relatively simple alternative for point-by-point radiofrequency ablation of paroxysmal AF and is associated with fewer incidences of fatal complications such as cardiac perforation. As experience with this new tool accumulates, the field faces new challenges in the form of rare compilations including gastroparesis, phrenic nerve palsy, atrioesophageal fistula, pulmonary vein stenosis, thromboembolism pericardial effusion, and tamponade.